Joint sparse model based data reconstruction algorithm for wireless sensor network - Yi-yin LIU; Guo-rui LI; Li TIAN (Tongxin xuebao)
The data of wireless sensor network has strong joint sparse characteristics,by utilizing compressed sensing theory,compressed data by joint encoding,and then reconstructed the data by joint decoding,the sensed data can be gathered with low computational cost.A synchronous subspace pursuit algorithm based on joint sparse model and com-pressed sensing theory was proposed.By utilizing the sparsity of the sensed data,it selected the correct joint subspace and reconstruct the original signal group accurately with fewer observations in a backtracking iterative manner.Com-pared with SCoSaMP algorithm and SP algorithm,the proposed algorithm presents better data reconstruction perform-ance under the conditions of different sparsity and sampling rate.